Molecular characterization of polyphenol oxidase between small and large leaf tea cultivars - Chen, Chung‑Tse; Yang, Chin-Ying; Tzen, Jason T. C. (Scientific reports, 2022)
Tea is a widely consumed beverage prepared using the fresh leaves of Camellia sinensis L. Tea plants are classified into small- and large-leaf varieties. Polyphenol oxidase (PPO), a crucial enzyme in tea manufacturing, catalyzes essential phenolic metabolites into different derivatives. To compare the molecular characteristics of CsPPO between cultivars, we cloned the full-length sequence of CsPPO cDNA from four representative tea cultivars in Taiwan. Amino acid sequence alignment analyses indicated that CsPPO is highly conserved. PPO exhibited similar enzymatic activity in different tea cultivars. Quantitative real-time polymerase chain reaction revealed no significant differences in the CsPPO transcript level between the small- and large-leaf varieties. However, tea harvested in summer and from low-altitude areas had a higher CsPPO transcript level than that harvested in winter and from high-altitude areas. Regulation of CsPPO by temperature was more significant in the small-leaf variety than in the large-leaf variety. The content of flavonoids and the expression of chalcone synthase, anthocyanidin synthase, and anthocyanidin reductase genes involved in the tea flavonoid biosynthesis pathway were higher in the large-leaf than in the small-leaf varieties, suggesting that the large-leaf variety had a higher antioxidative capacity than did the small-leaf variety. Our study compared the molecular properties of CsPPO between two tea varieties and clarified the physiological role of PPO in tea.